Analysis of obligatory measures against anthropic risks in Spanish football stadiums - López-Fernández, J.; García-Unanue, J.; Luis Felipe, J.; Burillo, P.; Sánchez-Sánchez, J.; Gallardo, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
Objectives: a) To develop a tool to check the level of compliance of Spanish football stadiums for the obligatory security measures against anthropic risks; b) to analyse and describe the current security state of six football stadiums (two per division). Methods: A dichotomic tool composed by 150 items divided in 10 categories was performed to analyse the situation of Spanish football stadiums. Results: There is a big heterogeneity in the percentage of compliance of the obligatory security measures among the stadiums analysed,from 2nd Division B (52%) to those of 2nd Division (85%) and 1stDivision (97%). The lower categories implemented are security plans (71%), high risk measures (69%), security documentation (67%) and technological means (61%). Conclusion: None of the six studied cases performed the 100% of the obligatory security measures. The tool used in this study can be useful for them to perform all the obligatory security measures.